Vegetation dynamics and climate variability in the Portoviejo river basin - Cuenca Zambrano, Karol K.; Pacheco Gil, Henry A. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Climate change is currently a global problem, as it significantly affects the dynamics of vegetation. The objective of this research is to analyze the influence of climate variability on the dynamics of vegetation in the Portoviejo river basin. The methodology consisted in the calculation of the NDVI with the use of multispectral images from the Landsat satellite and the analysis of the fluviometric records. The images were downloaded from the Earth Explorer geospatial platform with a spatial resolution of 30 m, images from the period 1998-2019 were selected to analyze their temporal trend. The historical fluviometric records of the Portoviejo station, of the National Institute of Hydrology and Meteorology were used. The results showed that the vegetation experienced a discontinuous greening trend, influenced by the variability of rainfall. A homogeneous trend was found in the spatial distribution of the NDVI, with dense and very dense vegetation cover in the upper part of the basin, as well as little or no cover in the lower part. The area with the greatest coverage corresponded to dense vegetation with a percentage higher than 30%.